IMPLEMENTASI NILAI-NILAI PANCASILA SEBAGAI UPAYA DALAM MENINGKATKAN NILAI GOTONG ROYONG DI MTS NEGERI 3 MATARAM - Hijrianti; Al Humairah Tsaniatul Fallah; Yolanda Alfira Febriana; Hannatun Nisa’; Elsa Mayora; Hulul Najamudin; Muh. Zubair (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The implementation of mutual cooperation is a very important thing to be implemented, especially in the school environment. However, in this modern era, the implementation of mutual cooperation has been minimally implemented. This research aims to determine the importance of implementing Pancasila values, especially in terms of mutual cooperation at MTs Negeri 3 Mataram. In this research, a qualitative approach was used with descriptive methods. To collect data, researchers conducted interviews, observations and also documentation. Not only that, in this case the researchers also used primary data and secondary data. Subjects and informants in the research This is a Civics teacher, and a class student representative at MTs Negeri 3 Mataram.The results of the research show that (1) the way to implement mutual cooperation at MTs Negeri 3 Mataram is by implementing previously existing programs, (2) The values contained in implementing mutual cooperation include: togetherness, responsibility, cooperation, as well as unity and oneness. (3) Challenges in implementing mutual cooperation can be seen from the opinions of teachers and students (4) The solution to overcoming challenges is by providing motivation to students, one of which is by providing additional value to students.